ACCUMULATION OF HEXOSES IN LEAF VACUOLES - STUDIES WITH TRANSGENIC TOBACCO PLANTS EXPRESSING YEAST-DERIVED INVERTASE IN THE CYTOSOL, VACUOLE OR APOPLASM - Sonnewald, Uwe; et al. (Planta, 1994)
The subcellular distribution of hexoses, sucrose and amino acids among the stromal, cytosolic and vacuolar compartments was analysed by a nonaqueous fractionation technique in leaves of tobacco (Nicotiana tobaccum L.) wild-type and transgenic plants expressing a yeast-derived invertase in the cytosolic, vacuolar or apoplasmic compartment. In the wild-type plants the amino acids were found to be located in the stroma and in the cytosol, sucrose mainly in the cytosol and up to 98% of the hexoses in the vacuole. In the leaves of the various transformants, where the contents of hexoses were greater than in wild-type plants, again 97-98% of these hexoses were found in the vacuoles. It is concluded that leaf vacuoles contain transporters for the active uptake of glucose and fructose against a high concentration gradient. A comparison of estimated metabolite concentrations in the subcellular compartments of wild-type and transformant plants indicated that the decreased photosynthetic capacity of the transformants is not due to an osmotic effect on photosynthesis, as was shown earlier to be the case in transformed potato leaves, but is the result of a long-term dedifferentiation of tobacco leaf cells to heterotrophic cells.
Keywords: AMINO ACID; HEXOSE UPTAKE; NICOTIANA; PHOTOSYNTHESIS; SUCROSE